Synthesis of Morphological-Variant ZnO nanostructures - Dikshit A.K.; Kamal; Singh A.K.; Rana J.S.; Singh R.K.; Mukhrjee N.; Chakrabarti P. (My University, 2025)
Nanostructures of zinc oxide have great potential in optoelectronics as well as in sensing applications. Here, we report the controlled and systematic growth of ZnO nanostructure by hydrothermal and vapor-liquid-solid (VLS) techniques, which can be used in various electronics and optoelectronic devices. The effect of various growth parameters (growth temperature, annealing time, the thickness of seed layer, to name a few) on the morphology of ZnO nanostructures has been studied. Ultra-long nanowires of length more than 300μm have been synthesized with aspect ratio around 10. © 2019 IEEE.